Alginate-Graphene Oxide Biocomposite Sorbent for Rapid and Selective Extraction of Non-Steroidal Anti-Inflammatory Drugs Using Micro-Solid Phase Extraction - Mohammad Salim Tabish; Nor Suhaila Mohamad Hanapi; Wan Nazihah Wan Ibrahim; Nor’ashikin Saim; Noorfatimah Yahaya (Universitas Gadjah Mada, 2019)
In this work, a bio-composite sorbent, alginate incorporated graphene oxide (Alg/GO) is prepared for the micro solid phase extraction of non-steroidal anti-inflammatory drugs (NSAIDs) from water samples. The sorbent was prepared in a suspended solution form at a ratio of 0.3:1 (w/v %) of graphene oxide (GO) and alginate (Alg). The chemical structure, morphology and surface area of the composite beads were characterized using Fourier Transform Infrared Spectroscopy (FT-IR), Scanning Electron Microscopy (SEM) and Brunauer–Emmett–Teller (BET). GO showed good miscibility and well dispersion through intermolecular hydrogen bonds and electrostatic interactions within the Alg matrix. The synthesized sorbent was applied for the determination of the selected drugs in a tap water sample using micro-solid phase extraction technique and was analyzed by high-performance liquid chromatography-ultraviolet detector (HPLC-UV). The results showed good linearity in the range of 10–1000 µg L–1 with correlation coefficients (r ≥ 0.9979), low detection limits (LOD) between 3.1–4.6 µg L–1, excellent relative recoveries in the range of 99.6–102.1% and good reproducibility (RSD ≤ 3.9%). Thus, these validated results showed that Alg/GO could be potential and useful as a bio-composite sorbent for micro-solid phase extraction for the analysis of targeted drugs from aqueous matrices.